PENGARUH PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA PADA SISWA SMKN 1 SURABAYA - Nindiya Kencana Duwi Pertiwi; Novi Marlena (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
Stronger entrepreneurship education is needed as an alternative job creation strategy given the high unemployment rate in Indonesia, especially among vocational high school (SMK) graduates. The purpose of this research is to examine how entrepreneurship education influences the entrepreneurial interest of eleventh-grade students at SMKN 1 Surabaya. This research uses a quantitative approach, and questionnaires are used to obtain data. The sample was selected using simple random sampling, totaling 187 students. Simple linear regression was used to analyze the data. The findings of this research indicate that entrepreneurial interest is significantly influenced by entrepreneurship education. This research highlights the importance of entrepreneurship education in shaping students' perspectives and preparing them for entrepreneurship.